Agricultural Mutual Insurance in Asia, Latin America, and the Caribbean: An Integrative Review of the Micro-Level Schemes - Rival Valcin; Tomohiro Uchiyama; Rika Terano; Dario S. Celestin; Bénédique Paul (Études Caribéennes)
Risk sharing is an excellent complement to risk reduction in the agricultural sector as two of the four main risk management strategies. Agricultural Mutual Insurance (AMI) is gradually becoming the most sustainable way to promote insurance products, specifically regarding farm insurance. This study aims to answer the following questions: What do successful schemes have in common? What triggers their particularities? Which approach still needs to be implemented that could be relevant? Additionally, how the Caribbean Catastrophe Risk Insurance Facility (CCRIF SPC) could be an opportunity for Caribbean countries such as Haiti to develop micro-insurance structures that effectively reach the farm level?To address these questions, we reviewed various papers on AMI schemes in Asia, Latin America, and the Caribbean. By searching for ‘Agricultural Insurance’ and ‘Mutual Insurance’ through trustworthy scientific databases such as ScienceDirect, Google Scholar, Scopus, and MDPI, we found 1091 hits by April 2024. We considered papers in English or French, published in journals with DOI or URL, official reports from countries or United Nations organizations, World Bank reports, books, and approved dissertations. Based on their suitability, we reviewed 58 papers, focusing on countries where micro-level mutual insurance has been implemented, such as Japan, China, India, Bangladesh, Nepal, and Mexico.Successful agricultural mutual insurance schemes share relevant features, such as local government involvement and low premium cost (≤ 10% of the sum insured). Without reinsurance, mutual insurance funds are inadequate against catastrophes; hence, they resort to the international market for reinsurance if not supported by government reinsurance. Mutual insurance is generally developed among farmers cultivating similar crops or belonging to a cooperative, where subscriptions can be individual or group-based. Agricultural loans often drive farm insurance, enhancing the agricultural credit portfolio. Countries with high disaster risk levels, like Haiti, Puerto Rico, Myanmar, and the Philippines, are potential recipients of funds from the World Bank Cat bond and the CCRIF. The study suggests that AMI implemented as a public-private partnership or following a cross-sector model is more likely to succeed.The study argues that Agricultural Mutual Insurance funds for disasters such as hurricanes and floods are feasible in Haiti and other vulnerable Caribbean countries, supported by financial structures like the World Bank CAT bond and the CCRIF SPC.The study provides insights into an innovative approach to be implemented in countries frequently experiencing disasters where governments cannot highly subsidize insurance premiums for farmers. While focusing on Haiti, the suggestions can also apply to Puerto Rico, Myanmar, and the Philippines. Specifically, the paper calls for Haitian leaders to include farmers as contributors and beneficiaries of the CCRIF SPC.This study develops a business model canvas describing the relevant features that ensure the viability and effectiveness of an AMI scheme. It is unique in providing a pattern based on successful models and highlighting what countries facing similar natural disaster exposures can learn from each other to enhance resilience and adaptation to climate risks.